The Influence of Nucleoside Reverse Transcriptase Inhibitors on Mitochondrial Activity, Lipid Content, and Fatty-Acid-Binding Protein Levels in Microglial HMC3 Cells - Katarzyna Lipke; Adriana Kubis-Kubiak; Agnieszka Piwowar (MDPI AG, 2023)
Despite the availability of a wide range of preventive measures and comprehensive treatment options following infection, the development of acquired immunodeficiency syndrome (AIDS) remains a persistent challenge. Nucleoside reverse transcriptase inhibitors (NRTIs) represent the most commonly utilized therapeutic approach, despite being on the pharmaceutical market for nearly four decades. During this time, a spectrum of side effects ranging from mild discomfort and hypersensitivity reactions to the more prevalent nephrotoxicity and hepatotoxicity has been documented. In light of these considerations, our study aimed to investigate the impacts of two NRTIs, lamivudine and zidovudine, on lipid metabolism in HMC3 microglial cells. Our findings revealed statistically significant reductions in the ATP levels (nearly 8%) and increased mitochondrial superoxide levels (around 10%) after 24 h of treatment with the maximum therapeutic concentration of zidovudine compared to the untreated microglial cells. Furthermore, the concentrations of fatty-acid-binding proteins 4 and 5 were significantly lower (approximately 40%) in the microglial cells that were exposed to NRTIs than in the untreated cells. Notably, the total lipid concentration within the microglial cells markedly increased following NRTI administration with a 13% rise after treatment with 10 µM lamivudine and a remarkable 70% surge following the administration of 6 µM zidovudine. These results suggest that the prolonged administration of NRTIs may potentially lead to lipid accumulation, posing a significant risk to the delicate homeostasis of the neuronal system and potentially triggering a pro-inflammatory response in microglial cells.